Congenital Mid Ureteric Valve Stenosis Revisited: Case Report and Review of the Literature - Elifranji, Mohammed; Elkadahi, Abderrahman; Charles, Adrian; Abbas, Tariq O. (Frontiers in Pediatrics, 2019)
Congenital mid ureteric valve is considered a very rare entity. Definitive preoperative diagnosis is a clinical challenge and most of the patients are misdiagnosed. Intraoperative identification is very important and ureteric segment excision and anastomosis is curative. We report here our experience clinical findings, radiological, histological workup, and operative management of a patient with midureteric valve. We do emphasize the importance of routine intraoperative retrograde pyelograrm to raise the suspicion of the presence of such rare pathologies.